2003
DOI: 10.1096/fj.02-0870fje
|View full text |Cite
|
Sign up to set email alerts
|

Ser‐256 phosphorylation dynamics of aquaporin 2 during maturation from the endoplasmic reticulum to the vesicular compartment in renal cells

Abstract: Aquaporin 2 (AQP2) phosphorylation at Ser-256 by protein kinase A (PKA) is a key signal for vasopressin-stimulated AQP2 insertion into the plasma membrane in renal cells. This study underscores the possible role of phosphorylation at Ser-256 in regulating AQP2 maturation. AQP2-transfected renal CD8 cells were incubated with brefeldin A (BFA) to accumulate newly synthesized AQP2 in the endoplasmic reticulum (ER), and AQP2 flow from ER to the vesicular compartment was analyzed after BFA washout. We found that a)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
62
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 42 publications
8
62
1
Order By: Relevance
“…It is located within the Golgi and has been suggested to phosphorylate AQP2 in this compartment ( Figure 5). 44 Other candidates are casein kinase II and protein kinase Ca, which phosphorylates S256 in vitro. 15,45 In IMCD cells, 4AD does not affect the phosphorylations at S261 and S269 (Figures 3 and 7), suggesting that the responsible kinases (e.g., p38 mitogen-activated protein kinases or Jun kinase 19 ) are insensitive to 4AD or that they catalyze the phosphorylations independently from V-ATPase activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is located within the Golgi and has been suggested to phosphorylate AQP2 in this compartment ( Figure 5). 44 Other candidates are casein kinase II and protein kinase Ca, which phosphorylates S256 in vitro. 15,45 In IMCD cells, 4AD does not affect the phosphorylations at S261 and S269 (Figures 3 and 7), suggesting that the responsible kinases (e.g., p38 mitogen-activated protein kinases or Jun kinase 19 ) are insensitive to 4AD or that they catalyze the phosphorylations independently from V-ATPase activity.…”
Section: Discussionmentioning
confidence: 99%
“…This might reflect cAMP-independent activation of AQP2 in AC6 Ϫ/Ϫ mice, which may involve V 2 R activation of phosphoinositide-specific phospholipase C 7 and PKA-independent AQP2 phosphorylation at S256. 36,37 These mechanisms may also contribute to intact AQP2 regulation in renal cortex of AC6 Ϫ/Ϫ mice. A prevalent dysfunctional missense single nucleotide polymorphism of AC6 with a reduced ability to form cAMP has been described with a frequency of approximately 3% in a white population.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the S256A mutation also inhibits hsc70 binding without causing membrane accumulation of AQP2, other factors must also be involved. Interestingly, it has been reported that impaired constitutive phosphorylation of Ser-256 (S256A) in the Golgi causes AQP2 routing to lysosomes rather than to AQP2-containing vesicles designated for exocytosis (55). Heat shock protein 70 (hsp70) has been well documented to be involved in endoplasmic reticulum-associated degradation (32,56), and facilitates the degradation of cystic fibrosis transmembrane conductance regulator in yeast (41)).…”
Section: Discussionmentioning
confidence: 99%